2006
DOI: 10.5507/bp.2006.031
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Plasticity and Its Implications for Focal Hand Dystonia

Abstract: Background:The exact origin of focal dystonias has not been elucidated so far. Aberrant plasticity of the brain cortex is suspected to be a crucial factor in the development of this group of movement disorders. The aim of this article is to summarize recent findings on the etiopathogenesis of focal hand dystonias with a focus on the role of abnormal cortical plasticity.Methods And Results: A search of the literature mainly from 1995 to 2005 was done using the PubMed and Ovid search engines. English-language ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…Both scales seemed to measure the benefit of DBS for dystonia effectively. Another interesting finding was that in some cases patients improved significantly more between the 6-and 12-month timepoints than between baseline and 6 months, supporting the notion of a delayed benefit in DBS for dystonia [6,9,12,51,55] and suggesting the possibility of a neuroplastic effect [39,42]. The blinded assessments from our study were lower in magnitude than the majority of those seen in previously published studies (see Tables 9, 10).…”
Section: Discussionsupporting
confidence: 44%
“…Both scales seemed to measure the benefit of DBS for dystonia effectively. Another interesting finding was that in some cases patients improved significantly more between the 6-and 12-month timepoints than between baseline and 6 months, supporting the notion of a delayed benefit in DBS for dystonia [6,9,12,51,55] and suggesting the possibility of a neuroplastic effect [39,42]. The blinded assessments from our study were lower in magnitude than the majority of those seen in previously published studies (see Tables 9, 10).…”
Section: Discussionsupporting
confidence: 44%
“…Task-specific focal hand dystonia (tspFHD) is an uncommon disorder of movement (Opavsky 2006) characterized by involuntary end range twisting postures of the fingers, wrist and forearm when performing a specific task. While the etiology of focal hand dystonia is considered idiopathic, most researchers and clinicians agree it is a multifactorial disorder which results from an interaction of intrinsic and extrinsic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, another study has shown that abnormal gray matter density in patients with BSP was related to the course of disease ( Suzuki et al, 2011 ). The conflicting results may be due to abnormal sensory motor plasticity ( Abbruzzese and Berardelli, 2011 ) and neuronal remodeling uncertainty ( Opavsky et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%